Reprogramming the tumor microenvironment to boost adoptive T cell therapy - Meza Pacheco, Maria Fernanda; Tai, Lee-Hwa (Frontiers in Immunology, 2025)
Adoptive T cell therapies (ACT) have revolutionized the management of hematologic malignancies; however, their efficacy in solid tumors remains limited. Accumulating evidence implicates the tumor microenvironment (TME) - a highly complex and immunosuppressive niche as a major barrier to their effectiveness. In this review, we propose that the next generation of ACT will require a fundamental shift from a reductionist focus on T cell engineering alone to an integrated approach that considers the interactions between immune cells and the TME. A comprehensive literature review identified several emerging strategies to enhance the efficacy of ACT, including reprogramming tumor vasculature, repolarizing immunosuppressive myeloid and stromal cells, leveraging oncolytic viruses to remodel antigen presentation, inducing acute sterile inflammation, and targeting the physical properties of the extracellular matrix. While many of these approaches remain in early-stage development, some have already progressed to clinical trials, indicating their potential for clinical translation. Additionally, we found that conventional therapies, such as surgery, chemotherapy, and radiotherapy, can be strategically integrated with ACT to improve therapeutic outcomes. These findings highlight a shift in the field toward more integrative approaches. Future advances will likely depend on reprogramming the TME to support T cell persistence and functions. Addressing these interconnected challenges will require closer collaboration between immunology, oncology, and bioengineering disciplines.